Sex Differences in Mesenchymal Stem Cell Therapy With Gelatin-Based Microribbon Hydrogels in a Murine Long Bone Critical-Size Defect Model - Ueno, Masaya; Zhang, Ning; Hirata, Hirohito; Barati, Danial; Utsunomiya, Takeshi; Shen, Huaishuang; Lin, Tzuhua; Maruyama, Masahiro; Huang, Ejun; Yao, Zhenyu; Wu, Joy Y.; Zwingenberger, Stefan; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Mesenchymal stem cell (MSC)-based therapy and novel biomaterials are promising strategies for healing of long bone critical size defects. Interleukin-4 (IL-4) over-expressing MSCs within a gelatin microribbon (µRB) scaffold was previously shown to enhance the bridging of bone within a critical size femoral bone defect in male Balb/c mice. Whether sex differences affect the healing of this bone defect in conjunction with different treatments is unknown. In this study, we generated 2-mm critical-sized femoral diaphyseal bone defects in 10–12-week-old female and male Balb/c mice. Scaffolds without cells and with unmodified MSCs were implanted immediately after the primary surgery that created the bone defect; scaffolds with IL-4 over-expressing MSCs were implanted 3 days after the primary surgery, to avoid the adverse effects of IL-4 on the initial inflammatory phase of fracture healing. Mice were euthanized 6 weeks after the primary surgery and femurs were collected. MicroCT (µCT), histochemical and immunohistochemical analyses were subsequently performed of the defect site. µRB scaffolds with IL-4 over-expressing MSCs enhanced bone healing in both female and male mice. Male mice showed higher measures of bone bridging and increased alkaline phosphatase (ALP) positive areas, total macrophages and M2 macrophages compared with female mice after receiving scaffolds with IL-4 over-expressing MSCs. Female mice showed higher Tartrate-Resistant Acid Phosphatase (TRAP) positive osteoclast numbers compared with male mice. These results demonstrated that sex differences should be considered during the application of MSC-based studies of bone healing.